2021
DOI: 10.1590/s1984-29612021065
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and community ecology of metazoan parasites in Pimelodus ornatus (Siluriformes: Pimelodidae) from the Amazonas River in Brazil

Abstract: The present study investigated the metazoan parasite community in Pimelodus ornatus from the Amazon River, in the state of Amapá (Brazil). Of 71 fish examined, 70.4% were parasitized by Demidospermus sp. (Monogenea), Cucullanus pinnai, Procamallanus (Spirocamallanus) inopinatus and Contracaecum sp. (Nematoda) and plerocercoids from Proteocephalidae gen. sp. (Cestoda). The dominance was of nematode species such as Procamallanus (S.) inopinatus and Contracaecum sp. The parasites showed a highly aggregated disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
4
0
1
Order By: Relevance
“…Infection by Contracaecum sp. was also reported in Pimelodus ornatus Kner, 1958(Lima et al, 2021 and C. asellus (Lima et al, 2023), collected in the same study area from which the specimens of E. pisonis were collected. However, there have been reports of occurrence of Contracaecum sp.…”
Section: Component Communities Of Metazoan Parasitessupporting
confidence: 59%
See 2 more Smart Citations
“…Infection by Contracaecum sp. was also reported in Pimelodus ornatus Kner, 1958(Lima et al, 2021 and C. asellus (Lima et al, 2023), collected in the same study area from which the specimens of E. pisonis were collected. However, there have been reports of occurrence of Contracaecum sp.…”
Section: Component Communities Of Metazoan Parasitessupporting
confidence: 59%
“…The presence of these endoparasites in E. pisonis may be related to its carnivorous feeding habit (Froese & Pauly, 2023), since infections by endoparasites have mainly been related to the diet of the host fish (Oliveira et al, 2017;Negreiros et al, 2019a, b;Lima et al, 2021Lima et al, , 2022Lima et al, , 2023. However, infection by the ectoparasite Ergasilus sp.…”
Section: Component Communities Of Metazoan Parasitesmentioning
confidence: 99%
See 1 more Smart Citation
“…2021), parasit ini ditemukan menginfestasi jenis ikan-ikan karang. Spirocamallanus (Gambar 5) sering ditemukan pada organ usus (Lima et al, 2021). Parasit ini memiliki buccale capsule panjang dan pipih yang terbagi menjadi beberapa katup dan 2 lateral dengan dinding tebal, dinding bagian dalam diperkuat dengan spiral bars, ekor menyempit di tengah dan dapat melengkung dengan dua duri apikal, memiliki sklerit berbentuk trisula menonjol ke arah dorsal, serta cincin sclerotized yang berada di antara katup dan kerongkongan (Kabata, 1985).…”
Section: Pemeriksaan Dan Identifikasi Parasitunclassified
“…For the Upper Juruá River region, recent studies on metazoan endoparasites have shown a great potential for diversity, where few studies carried out in these environments have already reported approximately 30 species of endoparasites (Lima et al ., 2021; Pacheco et al ., 2021; Virgilio et al ., 2021). However, none of these studies carried out in the Western Amazon analysed more than 13 host fish, which makes the present study the first to report the endoparasite fauna of metazoans of more than 50 species of host fish.…”
Section: Introductionmentioning
confidence: 99%